2018
DOI: 10.11646/phytotaxa.374.2.1
|View full text |Cite
|
Sign up to set email alerts
|

A new endophytic fungus, Tulasnella phuhinrongklaensis (Cantharellales, Basidiomycota) isolated from roots of the terrestrial orchid, Phalaenopsis pulcherrima

Abstract: A new species of endophytic fungus, described herein as Tulasnella phuhinrongklaensis, was isolated from a root of a terrestrial orchid, Phalaenopsis pulcherrima, in Phitsanulok Province, Thailand. This species is characterized by its cream to white colonies, branched chains of spherical to ellipsoid monilioid cells and absence of sclerotia. The uniqueness of the species was confirmed by a phylogenetic analysis of combined sequences of internal transcribed spacer (ITS) and large subunit region (LSU) of ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Regarding the other new species described here, the interspecific nucleotide divergence ranged from 5.4 to 41.6%. These values are comparable to or even higher than those found in previous studies on Tulasnella 33,34,38 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the other new species described here, the interspecific nucleotide divergence ranged from 5.4 to 41.6%. These values are comparable to or even higher than those found in previous studies on Tulasnella 33,34,38 .…”
Section: Discussionsupporting
confidence: 88%
“…Tulasnella species have complex morphological characteristics, but rarely form fruitbodies in situ or sexual structures in vitro [29][30][31][32][33] . As morphological characteristics are not sufficient to describe Tulasnella species 34 , molecular approaches have been used too 32,33,[35][36][37][38] . Species identification is mostly based on phylogenetic concordance of multiple unrelated genes/regions, but for this complex genus, the internal transcribed spacer (ITS) of the nuclear ribosomal DNA was shown to be highly suitable for species delimitation in Tulasnella 31,38 .…”
mentioning
confidence: 99%
“…Studies on OMF of epiphytic orchids are lacking despite their vast diversity, compared to terrestrial orchids (Yukawa et al 2009). While the roots of terrestrial orchids are usually subterranean, epiphytic orchids are commonly found growing in exposed environments and are prone to desiccation due to weather change (Rachanarin et al 2018;Freitas et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most epiphytic orchids studied tend to associate with either Ceratobasidium or Tulasnella (Yukawa et al 2009;Zettler et al 2013;Rachanarin et al 2018;Pujasatria et al 2020;Freitas et al 2020). However, more specifically, studies on OMFs of monopodial epiphytic orchids are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on OMF of epiphytic orchids are lacking despite their vast diversity, compared to terrestrial orchids (Yukawa et al 2009). While the roots of terrestrial orchids are usually subterranean, epiphytic orchids are commonly found growing in exposed environments and are prone to desiccation due to weather change (Rachanarin et al 2018; Freitas et al 2020). This leads to a presumably different fungal community compared to those of the underground.…”
Section: Introductionmentioning
confidence: 99%